Analisis Profitabilitas CV. Duta Nirwana Persada Agung - Putu Eka Nopiyani (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2021)
This study aims to determine the progress of the company from CV.Duta Nirwana Persada Agung (Lion Parcel Buleleng) achieving a profit, in running a company that works in the field of shipping services, of course we are very competitive with companies that already have names and also marketing that are quite experienced, so we have various kinds of obstacles in the company. However, there are many things that companies try to increase profitability, such as by holding a price promotion. At least the company is still quite good at running the company even with the competition in the current era. This research was conducted in CV. Duta Nirwana Persada Agung (Lion Parcel Buleleng) is located on the Sangsit Banjar Highway, Tegal Service. The data source used in this research is secondary data which is data collected from existing sources. In this study using CV financial statements. Duta Nirwana Persada Agung.